Spojrzenie z zewnątrz: literatura rosyjska w twórczości krytyka ukraińskiego Mykoły Jewszana - Korbicz, Halina (Studia Rossica Posnaniensia, 2012)
In the works of Mykola Yevshan (1890–1919), the leading critic of early Ukrainian modernism, the issue of Russian literature is of particular significance. An analysis of Yevshan’s papers shows that he referred both to the literature and philosophical thought of Western Europe as well as to Russian literary tradition. He particularly esteemed the achievements of Russian realism, considering them as having universal and ageless values. He hoped to find the answers to questions of an existential and social nature which troubled modernists in the works of the greatest Russian writers, Fyodor Dostoyevsky and Leo Tolstoy.